Bahasa dan Kebijakan Pembangunan Kelapa Sawit di Indonesia (Teori BREAK dan Linguistik Forensik) - Nesti, Meksi Rahma (Jurnal Hata Poda, 2022)
Language and Policy for Palm Oil Development in Indonesia, using BREAK theory and policy analysis studies with deep forensic linguistic dimensions solving language problems and oil palm development policies. BREAK is an acronym for Discourse Basis, Discourse Relations, Discourse Equilibrum, Actualization Discourse, and Sustainability of Discourse. BREAK theory is a theory created by Sawirman on the failure of Kant(ian), Hegelian, and Marx(ian) dialectics in mapping the typology of movements and structures of changes in reality and discourse accommodating. This theory aims to explain linguistic phenomena along with see the movement of the essence and spirit of discourse. Policy analysis has a linguistic dimension Forensics requires knowledge and understanding of various multidisciplinary sciences. Relation language, law, and political strategy are the main variables in the analytical study policy with a forensic linguistic dimension. The results of this research show that the essence of primary discourse is planning regarding palm oil development to be better in the future. The essence of secondary discourse is news about conflicts over palm oil development that are not going well. The spirit of the primary discourse is to make changes for the better, while the spirit from secondary discourse is information that shows existing policies being sent off did not go well on the field. Next, on to policy analysis with a forensic linguistic dimension, there is an intrusion or action of a criminal within making and establishing oil palm development policies. So, on In practice in the field, oil palm development often results in conflicts.Keywords: discourse, policy, essence, spirit, BREAK, forensic linguistics